Pengaruh Struktur Modal, Profitabilitas dan Kebijakan Hutang Terhadap Nilai Perusahaan - Ermi Solihatunnisa; Dani Sopian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to examine the effect of capital structure, profitability, and debt policy on firm value, with a focus on property and real estate sector companies. The type of research used is quantitative. Samples were taken using purposive sampling technique, namely sample selection based on certain predetermined criteria. The data used is secondary data in the form of annual reports obtained from companies for five years. This study collected 40 data from 8 property and real estate sector companies listed on the IDX during the 2018-2022 period. Data analysis was carried out using multiple linear regression with the help of the SPSS version 26 program. The results showed that simultaneously, the calculated F value was 3.481 with a significance value of 0.026, which is smaller than 0.05. This indicates that capital structure, profitability, and debt policy have a positive and significant influence on firm value. However, in partial analysis, it is found that only capital structure has a positive and significant influence on firm value with a significance value of 0.012 (<0.05), while profitability and debt policy have no significant influence with significance values of 0.273 (>0.05) and 0.149 (>0.05), respectively.